Affective temperament does not influence satisfaction after total knee arthroplasty. Issue 19 (May 2017) - Özdemir, Mahmut; Demirkale, İsmail; Şeşen, Hakan; Taşkesen, Anil; Okkaoğlu, Mustafa C.; Altay, Murat
Abstract: Background: Inherent temperament of the patient may predict the outcome of the surgical procedure. The purpose of this study was to ascertain whether negative affective temperament affects patient satisfaction and outcome measures. Methods: This prospective study included 143 patients who underwent total knee arthroplasty for primary arthrosis. Preoperatively, the Memphis, Pisa, Paris and San Diego-Auto questionnaire was used to define the temperament of the patient. Knee Society Score (KSS) and short form-36 (SF-36) outcome measures were used to evaluate the functional outcome. Results: No relationship was determined between temperament and satisfaction ( P  = .734). Overall, the satisfaction rate of the procedure in our patients was 93%. The KSS improved from a mean of 47.9 to 70.1 (F = 124.275; P a  < .05) and the SF-36 physical component summary, and SF-36 mental component summary scores improved to a mean of 39.5 and 43.04 points, respectively. Conclusion: Temperament was not found to have any effect on patient satisfaction. However, patient satisfaction was directly related to better functional outcomes.